Demands for perimenopausal health care in women aged 40 to 60 years—a hospital-based cross-sectional study in Shanghai, China. Issue 2 (February 2019) - Huang, Cheng; Zheng, Yanwei; Zhu, Liping; Li, Yang; Du, Li; Tao, Minfang; Xu, Biao
Abstract: Objectives: The aim of the study was to describe the major complaints of menopausal symptoms among middle-aged women who initiated healthcare seeking for menopausal symptoms and to understand the factors influencing women's decisions to seek perimenopausal health care in Shanghai, China. Methods: A cross-sectional study was performed in five hospitals in Shanghai. Women aged 40 to 60 years at their first visit to the perimenopausal outpatient departments/clinics were investigated in person over a 3-month period. Information on sociodemographics, menopausal symptoms, and experiences in seeking perimenopausal health care was collected using a structured questionnaire. Menopausal symptoms were assessed with the modified Kupperman Menopausal Index (mKMI). Results: A total of 316 women were enrolled in the study, with an average age of 50.5 years (SD: 5.1 y). The prevalence of menopausal syndrome (mKMI >6 points) was 80%, with 7% of the cases being severe. The top five reported symptoms were hot flushes/sweating (62%), fatigue (54%), sleep disturbance (51%), mood swings (40%), and joint/muscle pain (40%). The median interval between symptom occurrence and seeking perimenopausal health care was 5.0 months (IQR: 2.0-23.3 mo). Cox regression analysis revealed that older age, no health insurance, employment, multiple symptoms, sleep disturbance, urinary incontinence, and visits to nonspecialized departments were significantly associated with a longer delay in seeking perimenopausal health services ( P  < 0.05). Conclusions: The prevalence of menopausal syndrome was relatively high among 40- to 60-year-old women who initiated healthcare seeking in Shanghai. Months of delay occurred before they sought perimenopausal health services. The delay was related to age, the nature and number of symptoms, working status, and health insurance. Improvement of the menopausal health knowledge in Chinese middle-aged women may lead to more timely healthcare seeking. Professional and accessible perimenopausal health services are in high demand in Shanghai.